Lipid Metabolism in Patients with End-Stage Renal Disease: A Five Year Follow-up Study - Dusejovska, Magdalena; Stankova, Barbora; Vecka, Marek; Rychlíkova, Jana; Mokrejsova, Magdalena; Rychlík, Ivan; Zak, Ales (Current Vascular Pharmacology, 2018)
Background: Patients with end-stage renal disease (ESRD) exhibit high morbidity as well as mortality for atherosclerotic cardiovascular diseases (CVD). Therefore, we investigated differences in individual lipoprotein classes and subclasses in ESRD patients under chronic high volume hemodiafiltration (HV-HDF) in comparison with a control group. We also assessed the prognosis of these patients and analyzed these parameters after 5 years follow-up. Methods: 57 patients and 50 controls were enrolled. We analysed high density (HDL) and low density (LDL) lipoprotein subfractions using the Quantimetrix Lipoprint(R) system. Subfractions were correlated with selected clinical-biochemical parameters including risk factors for atherosclerotic CVD at the beginning of and after 5 years follow-up. Results: Fourteen patients survived the 5-year follow-up. Follow-up results revealed a shift toward smaller HDL subfractions. In lipoproteins carrying apolipoprotein B, there was a shift of cholesterol from very low density (VLDL) to intermediate density (IDL) lipoproteins and LDLs. Hypolipidaemic therapy did not influence lipoprotein profiles in HV-HDF patients. Conclusion: 1. HV-HDF patients exhibit specific lipid profiles with elevated triacylglycerol, low HDL and LDL and higher content of cholesterol in remnant particles (VLDL and IDL) at the expense of large LDL. HDL subfractions were linked to the number of risk factors for CVD in the control group only. 2. Baseline lipoprotein profiles did not differ between survivors and non-survivors. Non-survivors had higher CRP and lower HDL-C. 3. During the 5 year follow-up period, cholesterol in HDL particles and lipoproteins carrying apolipoprotein B redistributed in survivors towards smaller particles, thus resembling the profile of control patients.
Keywords: lipoproteins